KONSEP EKONOMI DALAM PERSPEKTIF AL QUR’AN - Galuh Nashrullah Kartika (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2016)
The study of economics in principle talking about human behavior as consumers, distributors and manufacturers, while the primary object is human behavior. The long journey of human conduct turns conventional economics in a very troubling situation, because of Western economic system serve the private interests and not serve Allah SWT. Through this article, the author would like to invite readers to go back to the Qur'an as a guide, to uncover the economic principles that were examined in it by the method of Maudlu'i interpretation, namely, first, an inventory of the verses related to the economic problems that will be discussed, either based on the keywords or the content of general and specific paragraph. Secondly, interpreting the verses are both based on the order of verses in order of descent-based manuscripts or letters. Third, do konstektualisasi in economic reality. The results of this study is first, in carrying out the transactions Islam Educate people to be honest, trust, fair, discipline, keeping promises and be responsible (Q.S. Al Baqarah (2): 282-284). Second, optimalization of working, steadfastness, do not do mischief, and put the concept of beneficiaries as a production orientation (Surah al-Baqarah (2): 22, al-Nahl (16): 5-9, 10-11 , 14, 18, 65, 66, 67, 68, 69.70, 80, 81 al-Maidah (5): 62-64). Third, In the Islaamic norm, the consumption of which is the next part of the economic activity let to be frugal in using the property, spend treasure with kosher, and running a chain of economy through legal means (Surah Al-Baqarah (2): 168, 172, 187, al-Maidah (5 ): 4, 88, al-An'am (6) 118, 141, 142, al-A'raf (7): 31, 160, 161, al-Anfal (8): 69, an Nahl (16): 114, al-Isra (17): 26-28, Toha (20): 54, 81, al-Hajj (22): 28, 36, al-Mukminun (23): 51, Saba (34): 15, at -Tour (52): 19 al-Mulk (67): 15, al-Haqqah (69): 24, al-Mursalat (77): 43, 46). Islamic economic behavior is not only dominated by natural values possessed by each individual, but there is also a value outside the human self which then formed the economic behavior. This value is believed to be the main guidance in life and human life, the values that are taught in the Qur'an as a guide for each individual.